HIV/AIDS message exposure, knowledge, attitudes and safe practices among adolescent Islamiyya girls in Northeast Nigeria - Muhammad, Hamid Adamu (2018)
Exposure to HIV/AIDS messages especially on the mass media among adolescents in sub Saharan Africa has been reported as abysmal in the early 2000s, but now given the growth in infrastructure and development in technology and program appeal, there emerges a need for reassessment. Given that communication particularly through the media is considered a major preventive strategy, this study was set out with the objective of investigating the message exposure, knowledge, attitudes and practices (KAP) on HIV/AIDS of adolescent Islamiyya girls as potential mothers in Northeast Nigeria a predominantly Muslim society. Mediating role of HIV/AIDS knowledge and HIV/AIDS attitudes between HIV/AIDS message exposure and HIV/AIDS safe practice, and the moderating role of formal schooling in a structural model were verified. The study also investigated the girl’s interpretations of HIV/AIDS messages because generally campaigns over the mass media are susceptible to being misinterpreted by different audiences. This study as well content analyzed the Daily Trust newspaper to determine its pattern of the coverage of HIV/AIDS. Questionnaire survey was administered to 487 respondents selected through multi stage probability sampling, whose data were analyzed by descriptive statistics and PLS Structural Equation Modeling. The qualitative data on the interpretations of the girls’ of HIV/AIDS major campaign messages was drawn through focus group discussion with 24 informants among the girls. Focus group discussion is relevant because the informants are being investigated on a focused topic, which is their negotiated meanings of HIV/AIDS campaign messages. Again, all similar studies of message exposure and HIV/AIDS KAP only investigated the extent of message exposure, thereby leaving a big gap on the essence or meaning the audience attach to the messages. A hundred and seventy HIV/AIDS stories of Daily Trust were content analyzed for the period of 3.5 years (1st January 2013-31st June 2016) The survey found that majority of the respondents reported mass media as their main sources of information on HIV/AIDS. The tested structural model shows while HIV/AIDS message exposure was not a significant predictor of HIV/AIDS safe practice and favorable attitudes, it was a significant predictor of HIV/AIDS knowledge, and HIV/AIDS knowledge was a significant predictor of both HIV/AIDS favorable attitudes and safe practice. HIV/AIDS knowledge was a significant mediator in the model and formal schooling a significant moderator on HIV/AIDS practice. It is concluded that HIV/AIDS message exposure is a necessary but not a sufficient precursor for HIV/AIDS safe practice. It is also revealed that the girls interpreted the HIV/AIDS messages (1) in literal sense, (2) in connotative sense contrived in consonance with Islamic principle, (3) as gender discrimination, (4) as protection, and (5) as legitimization for adultery. Majority of the Daily Trust’s HIV/AIDS stories were hard news, mostly dedicated on the theme of care for people living with HIV/AIDS and mostly neglecting rural areas in their coverage. Almost all the stories were buried in inside pages and only. Overall, evidence from this study suggests that the Hierarchy of Effects model fits better within the Media Limited Effects models compared to linear transmission models of behavior change. It is thus concluded that mass media are a necessary but not a sufficient precursor of HIV/AIDS practice, and HIV/AIDS messages are prone to misinterpretations.